2000
DOI: 10.1161/01.atv.20.7.1842
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of von Willebrand Factor

Abstract: Abstract-Data from the Whitehall II Study and others have demonstrated a role for the metabolic syndrome and fibrinogen underlying the association between social position and coronary heart disease. In this study, we examined the role of an additional hemostatic factor and marker of endothelial dysfunction, von Willebrand factor (vWF). Four thousand five hundred and forty-eight men and 1837 women were examined in the third phase of the study, which took place between 1991 and 1993. Employment grade was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 26 publications
8
36
1
1
Order By: Relevance
“…Kumari and colleagues (46) reported that vWF was higher in male smokers than in male nonsmokers and men who smoked more than 21 CPD had statistically significantly elevated levels of vWF compared with those who smoked fewer CPD. No such differences were found between female smokers as reported by Kumari and colleagues.…”
Section: Discussionmentioning
confidence: 97%
“…Kumari and colleagues (46) reported that vWF was higher in male smokers than in male nonsmokers and men who smoked more than 21 CPD had statistically significantly elevated levels of vWF compared with those who smoked fewer CPD. No such differences were found between female smokers as reported by Kumari and colleagues.…”
Section: Discussionmentioning
confidence: 97%
“…The same standard pool of citrated, platelet-poor plasma from 120 donors was used throughout the study as a control calibrated against the fourth British Standard for Blood Coagulation Factors, Plasma Human 89/592 (established 1990) from the National Institutes for Biological Standards and Control. The coefficient of variation for the measurement of vWF levels was 16% (Kumari et al, 2000). vWF concentration was expressed in international units per deciliter.…”
Section: Whitehall II Study (Whii)mentioning
confidence: 99%
“…There is a grade gradient in vWF, and the levels of vWF are associated with other confounding factors, including alcohol intake and fasting glucose level. 17 Data from this and other studies have also indicated that individuals and in particular men who were short sleepers were more 6 likely to be in the lowest employment grades and unmarried. To investigate the association between sleep and hemostatic factors, we adjusted for either employment grade or marital status (the latter showing a greater variation with sleep) and other potential confounding factors.…”
Section: Discussionmentioning
confidence: 54%
“…17 The coefficient of variation was 16.1%. A spline fit was applied to the results to determine the effect of time of sample collection on mean level.…”
Section: Analysis Of Vwfmentioning
confidence: 94%